DGS-Based Modules: Difficulty Aspects of Studying Geometry at University Level - Istikomah, Endang; Juandi, Dadang; Suryadi, Didi; Prabawanto, Sufyani (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2022)
This study aims to ensure that geometry is the most difficult subject to understand, aspects of the difficulty of learning geometry for students, and suggestions for reducing difficulties. This study uses an exploratory mixed methods design. Students of mathematics education teacher candidates in semesters 3-7 as research subjects were selected by purposive sampling. The data collected in this study used a questionnaire technique, interviews, and the value of learning outcomes for the last 4 years. The results showed that geometry is the most difficult subject, the external learning difficulties factor is dominated by the aspects of the material and learning methods. In addition, references, media, and online learning are also discussed factors. Meanwhile, students' learning difficulties internally from the aspect of motivation and intelligence. One solution suggested to educators is to take advantage of the collaboration of DGS with the Geometry module in learning in dealing with learning difficulties.Tujuan penelitian ini adalah untuk memastikan bahwa geometri merupakan matakuliah yang paling sulit dipahami, aspek kesulitan belajar geometri pada mahasiswa dan saran untuk mengurangi kesulitan. Penelitian ini menggunakan Eksploratory mixed methods design. Mahasiswa calon guru pendidikan matematika semester 3-7 sebagai subjek penelitian dipilih dengan teknik purposive sampling. Teknik pengumpulan data menggunakan teknik angket, wawancara dan nilai hasil belajar selama 4 tahun terakhir. Hasil penelitian menunjukkan bahwa geometri merupakan matakuliah paling sulit, faktor kesulitan belajar secara eksternal didominasi dari aspek materi dan metode pembelajaran. Selain itu, referensi atau bahan ajar, media dan pembelajaran secara daring juga menjadi factor yang dibahas. Sedangkan kesulitan belajar mahasiswa secara internal dari aspek motivasi dan intelegensi atau kemampuan keruangan. Salah satu solusi yang disarankan kepada pendidik adalah memanfaatkan DGS yang dikolaborasikan dengan Modul Geometri dalam pembelajaran untuk menangani masalah kesulitan belajar.